How women's experiences and perceptions of care influence uptake of postnatal care across sub-Saharan Africa: a qualitative systematic review - Caitlin Lythgoe; Kirsty Lowe; Mary McCauley; Hannah McCauley (BMC, 2021)
Abstract Background The burden of maternal and neonatal morbidity and mortality is a global health concern with the highest burden documented after childbirth in women and babies living in sub-Saharan Africa. To date, there is limited information on the quality of postnatal care and/or whether evidence-based interventions to improve postnatal care in a way that meets the specific health needs of each mother and her baby have been lacking. There is also limited data related to how quality of care (respectful or disrespectful) influences women's decision to access postnatal care. Objective To systematically review available qualitative evidence for how quality of care (respectful or disrespectful) influences perceptions and experiences of, and decisions to, access postnatal care for women living in sub-Saharan Africa. Search strategy CINAHL plus, Cochrane library, Global Health, Medline, PubMed, Web of Science were searched from 2009-2019. Grey literature was searched on Google Scholar. Selection criteria Qualitative literature in English describing women's perceptions and experiences of the quality of care they received after childbirth and how this influenced their perceptions of and decisions to access postnatal care. Data analysis Thematic analysis was performed to extract subthemes and themes. Outcomes were themes from the qualitative data used to form a thematic synthesis. Results Fifteen studies were included with data from 985 women interviewed face-to-face across eight countries. Descriptions of respectful care included healthcare providers being kind, supportive and attentive to women's needs. Women described preferring healthcare services where the healthcare providers communicated in a respectful and caring manner. Descriptions of disrespectful care included verbal and/or physical abuse and power imbalances between women and healthcare providers. Some women were denied postnatal care when attending a healthcare facility after giving birth at home. There is evidence to suggest that vulnerable women (adolescents; women with poor socioeconomic status; women who are HIV positive) are more likely to receive disrespectful care. Conclusions This systematic review describes how aspects of respectful and disrespectful maternity care influence women's perceptions and experiences of, and decisions to access postnatal care services. There is a need for a renewed focus to prioritise respectful maternity care and to sustainably provide good quality postnatal care to all women and their babies in a way that meets their expectations and health needs.